Association of breast feeding with early childhood dental caries: Japanese population-based study. Issue 3 (20th March 2015) - Kato, Tsuguhiko; Yorifuji, Takashi; Yamakawa, Michiyo; Inoue, Sachiko; Saito, Keiko; Doi, Hiroyuki; Kawachi, Ichiro
Abstract : Objectives: We investigated the association between breastfeeding duration during the first half year of life and the risk of early childhood caries from the age of 30 to 66 months in Japan. Design: Observational study of a longitudinal survey. Setting: A secondary data analysis of the Japanese Longitudinal Survey of Babies in the 21st Century. Participants: 43 383 infants at the age of 6 months. Outcome measures: Early childhood caries—defined as a child's visit to a dentist for treatment of dental caries during the past 12 months—was ascertained from the caregiver from the age of 30 months in the survey. We estimated the risk of dental caries each year according to duration of breast feeding using logistic regression analyses. We controlled for a set of biological factors (birth weight, sex, parity and maternal age at delivery) and socioeconomic factors (maternal educational attainment and smoking status, marital status at delivery, family income and region of birth and residence). Results: We found that infants who had been breast fed for at least 6 or 7 months, both exclusively and partially, were at elevated risk of dental caries at the age of 30 months compared with those who had been exclusively formula fed. Adjusted ORs were 1.78 (95% CI, (1.45 to 2.17)) for the exclusively breastfed group and 1.39 (1.14 to 1.70) for the partially breastfed group. However, the associations became attenuated through the follow-up period and were no longer statistically significant beyond the age of 42 months for the partially breastfed group and beyond the age of 54 months for the exclusively breastfed group. Conclusions: We found an association between breast feeding for at least 6 or 7 months and elevated risk of dental caries at age 30 months. However, the association became attenuated as children grew older.